Impact of natural parameters on rock glacier development and conservation in subtropical mountain ranges. Northern sector of the Argentine Central Andes - Forte, Ana Paula; Villarroel, Cristian Daniel; Esper Angillieri, María Yanina
This paper presents a detailed rock glacier inventory used in determining how the various natural parameters affect a mountain periglacial environment. This study was undertaken in a northernmost sector of the central Argentine Andes, in an area stretching between 31°02´ and 31°22´ S latitude. This is a high and arid subtropical region where permafrost and cryogenic processes are predominant, featuring as well as a large number of rock glaciers and associated periglacial landforms. Rock glaciers inventory was based on geomorphological characterization with optical remote sensing data and field description information. The study region covers 630 km2, with 3,25 % of this area showing 402 rock glaciers and protalus rampart features. In total, 172 rock glaciers have been identified, 48 of which are considered active. In such a sector, the protalus rampart range shows the largest landform occurrences, though fossil and inactive rock glaciers are usually larger and are developed over a larger attitudinal distribution. Based on previous studies, we have considered that the study of active rock glaciers is an effective approach to assess the current state of periglacial environment evolution. Therefore, we analysed their spatial distribution and their relationship through different variables, by resorting to statistical analysis and a frequency ratio method. The chosen natural parameters were: Lithology, Elevation, Latitude and Longitude,Aspect, Slope and Annual Potential Solar Incoming Radiation. Analytical results have demonstrated that active rock glaciers landforms lie above 3.600 m.a.s.l. elevations, on 11° to 28° slopes with predominating south facing aspect and relatively low solar radiation. The statistical analysis shows that elevation, lithology and aspect are the most influencing factors for current periglacial environment development while rock glacier conservation is mainly controlled by lithology. On the study area, the annual potential solar radiation show high values but there is not any significant ...